Packing, moisture and environment for conservation of ‘jabuticatree açu’ seeds during storage - Hossel, Cristiano; Hossel, Jéssica Scalet Alves de Oliveira; Wagner Júnior, Américo; Dotto, Marcelo; Pirola, Kelli; Citadin, Idemir (Comunicata Scientiae, 2018)
The objective of this study was to evaluate the viability of ‘jabuticaree açu’ [Plinia cauliflora (DC.) Berg] seeds according to water loss and packaging conservation conditions. Two experiments were carried out at UTFPR - Dois Vizinhos Campus, Parana State, Brazil. For the first experiment, the seeds were submitted to the hydro conditioning process by soaking in water during 24 hours with subsequently storage in a BOD chamber at 25°C for 0, 12, 24, 36, 48, 60, 72, 84 and 96 hours. This experiment was conducted in a completely randomized design with four replications of 50 seeds each. For the second experiment the seeds were separated into three lots: PET® bottles with lids, kraft® paper bags at room temperature and in cold storage (6°C±1°C). Each lot was stored during 0, 5, 10, 15, 20, 25, 30, 60, 90, 120 and 150 days. The experiment was carried out in a completely randomized design, in a 3x11 factorial (storage location x storage period), with four repetitions of 50 seeds each. Plinia cauliflora seeds present storage capacity of 96 hours at room temperature without loss of germination capacity, when previous hydro conditioning was carried out. Storage using Pet® bottles at room temperature for up to 25 days allows seeds viability.